A study on evaluation of upper gastrointestinal endoscopic findings in established acute pancreatitis patients in tertiary care hospital - Prakash, G. V.; Kumar, A. Satish; Kumar, M. Vijay; Nagamuneiah, S.; Rajaram, G.; Sabitha, P.; Shariff, S. A. (International Surgery Journal, 2019)
Background: The objective of the study was to enumerate the different mucosal lesions in established acute pancreatitis on upper gastrointestinal endoscopy. Methods: We prospectively conducted a study on patients with acute pancreatitis above the age of 18 year having aute onset of typical abdominal pain consistent with acute pancreatitis, or Serum amylase and/ or lipase level >2 times the upper limit of normal or characteristic findings of acute pancreatitis on an abdominal computed tomography (CT) scan or on ultrasonography. Patients who are unfit or not willing for endoscopy or had endoscopy –proved peptic ulcer disease in the recent 3 months were excluded. Results: In the present study, the most common age group presenting with acute pancreatitis was between 30 to 60 years. In present study, alcohol is the more common cause for acute pancreatitis, accounting for 90% of the study group and pain abdomen is the most common symptom. In the present study, CT scan is most (100%) confirmatory diagnostic investigation of acute pancreatitis. In the present study, out of 80 patients with acute pancreatitis who were subjected to OGD, 72 patients had positive upper gastrointestinal finding. In patients having significant OGD findings, gastritis (42 cases, 52.5%) accounted for the most common finding. In the present study the prevalence of H. pylori infection is only 26.3%. Enlarged pancreas is the only CT finding in most cases. Conclusions: Esophagitis and gastric and duodenal ulcers are common endoscopic findings in acute pancreatitis. They are not correlated with the severity of pancreatitis.